Perspectives for sustainable Prunus africana production and trade - Ingram, V.J.; Loo, J.; Dawson, I.; Vinceti, B.; Duminil, J.; Muchugi, A.; Awono, A.; Asaah, E. (Wageningen University & Research, 2015)
This brief documents current knowledge about pygeum (Prunus africana). It aims to inform decision makers in governments in producing and consumer countries, international and civil society organisations and researchers, about sustainable (international) trade and governance of the species.